O tempo multidimensional nos quadrinhos: um estudo das estratégias narrativas em Here, de Richard McGuire - Silva, Cátia Ana Baldoino da (2019)
The focus of this research is the analysis of the structure and the narrative resources used to represent time in Here (1989), a short comic story written by Richard McGuire. Structured from a fixed point of view it shows, in multiple, fragmented and multilinear forms, the evolution and the events ocurred durging millions of years in the portrayed space. Such a structure demands a multiple, multilinear and fragmented reading from which the reader can construct the meanings of history. Its analysis, thus, enables a better understanding of the comic language, especially with respect to its temporal dimensions. The choice of theoretical approach, guided by the theme and object of study, provides a dialogue between literary theory and the studies of comics (ELIAS, 1998; NUNES, 1995; TODOROV, 2013; EAGLETON, 2006; GROENSTEEN, 2015; EISNER, 1999 and 2005). It is expected, with this intersection, to contribute to a better understanding about the possibilities and potentialities of graphic narratives.